Circular RNA circRIMS1 Acts as a Sponge of miR-433-3p to Promote Bladder Cancer Progression by Regulating CCAR1 Expression - Feifan Wang; Mengjing Fan; Yueshu Cai; Xuejian Zhou; Shengcheng Tai; Yanlan Yu; Hongshen Wu; Yan Zhang; Jiaxin Liu; Shihan Huang; Ning He; Zhenghui Hu; et al. (Elsevier, 2020)
Circular RNAs (circRNAs), a subclass of noncoding RNAs, are reportedly involved in the progression of various diseases. However, the exact role of circRIMS1, also termed hsa_circ_0132246, in human bladder cancer remains unknown. By performing RNA sequencing comparing bladder cell lines and normal uroepithelial cells, circRIMS1 was selected as a research object. We further verified by qRT-PCR that circRIMS1 is upregulated in both bladder cancer tissue and cell lines. Proliferation, colony-formation, Transwell migration, invasion, apoptosis, western blotting, and in vivo experiments were utilized to clarify the roles of circRIMS1, microRNA (miR)-433-3p, and cell cycle and apoptosis regulator 1 (CCAR1). For mechanistic investigation, RNA pulldown, fluorescence in situ hybridization (FISH), and luciferase reporter assay confirmed the binding of circRIMS1 with miR-433-3p. Inhibition of circRIMS1 suppressed the proliferation, migration, and invasion of bladder cancer cells both in vitro and in vivo. Moreover, the circRIMS1/miR-433-3p/CCAR1 regulatory axis was confirmed to be responsible for the biological functions of circRIMS1. Taken together, our research demonstrated that circRIMS1 promotes tumor growth, migration, and invasion through the miR-433-3p/CCAR1 regulatory axis, representing a potential therapeutic target and biomarker in bladder cancer.